A Novel Fibrinolytic Protein From Pheretima vulgaris: Purification, Identification, Antithrombotic Evaluation, and Mechanisms Investigation - Liu, Hai; Yang, Jianqiong; Li, Yamei; Ma, Yunnan; Wang, Wenjie; Zhong, Wanling; Li, Pengyue; Du, Shouying (Frontiers in Molecular Biosciences, 2022)
Thrombotic diseases have been considered as the major causes of death around the world. The treatments with thrombolytic drugs such as recombinant tissue-plasminogen activator, urokinase, and streptokinase are reported to have a life-threatening bleeding tendency. On the contrary, lumbrokinase, identified from Lumbricus rubellus, is specific to fibrin and does not cause excessive bleeding. It possesses fibrinolytic activity and activation of plasminogen to dissolve fibrin. Hence, the purification of fibrinolytic protein monomer from earthworm, and antithrombotic evaluation and investigation of mechanisms are needed. In this study, a novel fibrinolytic protein EPF3, with strong fibrinolytic activity, was purified from Pheretima vulgaris by ion exchange and size exclusion chromatography. SDS PAGE, bottom-up proteomics analysis, de novo sequencing, and CD analysis were carried out for identification and characterization of it. EPF3, with a molecular weight 25136.24 Da, consisted of 241 amino acids, and contained various forms of secondary structures, including α-helix (3.9%), β-sheet (42.8%), β-turn (21.2%), and random coil (32.1%). It was a trypsin-like serine protease and stable at pH 7.0 to 11.0 and below 40℃. EPF3 was confirmed to possess an antithrombotic effect by ex vivo clot lysis test and fibrinogen-thrombintime (Fib-TT) assay. The three-dimensional structure of EPF3 was predicted by SWISS-MODEL. Molecular docking analysis predicted that EPF3 could directly interact with antithrombotic target proteins (fibrin, fibrinogen and plasminogen ), which was further confirmed by further studies. The antithrombotic mechanism of EPF3 was clarified to be outstanding direct fibrinolysis, fibrinogenolytic activity and certain activation of plasminogen. EPF3 possesses the prospects of developing a promising antithrombotic agent.